2017
DOI: 10.21699/jns.v6i2.482
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Perforated Appendicitis Masquerading as Necrotizing Enterocolitis

Abstract: A preterm neonate underwent emergent laparotomy for presumed necrotizing enterocolitis (NEC). Intraoperatively, neonatal perforated appendicitis (NPA) was encountered. This may represent a form of NEC localized to the appendix. A high index of clinical suspicion and early laparotomy are recommended.Key words: Neonatal perforated appendicitis; Neonatal appendicitis; Necrotizing enterocolitis; Localized NEC CASE REPORTAn 1890-g male product of a dichorionic-diamniotic twin intrauterine pregnancy was born at 36 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
3
0
4
Order By: Relevance
“…NA is usually reported in associated with Hirschsprung's Disease or NEC, and rarely as isolated or as an Amyand hernia. [1,9,11,15,18] Some authors believe that NA may be associated with cystic fibrosis [5]. In this study, 10 patients had NA secondary to NEC; none of our patients had Hirschsprung's Disease (HD) or Cystic Fibrosis (CF).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…NA is usually reported in associated with Hirschsprung's Disease or NEC, and rarely as isolated or as an Amyand hernia. [1,9,11,15,18] Some authors believe that NA may be associated with cystic fibrosis [5]. In this study, 10 patients had NA secondary to NEC; none of our patients had Hirschsprung's Disease (HD) or Cystic Fibrosis (CF).…”
Section: Discussionmentioning
confidence: 72%
“…Most studies have not shown reliable investigations/biomarkers in the diagnosis of NA. [7,10,11,15,18] Plain radiographs, although not diagnostic of appendicitis, are helpful in detecting complications such as perforation. [1]Spiral computed tomography can also be a very useful diagnostic tool; [15][16][17] however, is less frequently used, which may be due to avoidance of radiation, higher cost, and development of early peritonitis also directs for early surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Diversos reportes han destacado la similitud clínica con enterocolitis necrosante, por lo que se ha plantea-do tanto una posible asociación entre ambas condiciones, como que la apendicitis en el recién nacido podría estar en el contexto de la ella 2,5,6,8 . Otras condiciones asociadas que se han observado son la enfermedad de Hirschsprung, fibrosis quística, íleo meconial, hernia inguinal uni o bilateral, o infección por citomegalovirus 3,4 , aunque en algunas series reportadas no se ha demostrado la asociación con enfermedad de Hirschprung ni fibrosis quística 9 .…”
Section: Discussionunclassified
“…En la actualidad el manejo quirúrgico es mayoritariamente laparoscópico 14 y tiene objetivos tanto diagnóstico como terapéutico. La precocidad del diagnóstico tiene gran importancia en el pronóstico, tanto en las complicaciones sépticas como en la sobrevida, considerando que por las características clínicas el diagnóstico suele ser tardío 1,4,5,6,14,15 . Algunas propuestas de tratamiento conservador, con antibióticos y sin cirugía, hasta hoy, no cuentan con evidencia en recién nacidos 16 .…”
Section: Discussionunclassified
See 1 more Smart Citation